DDTs-induced antioxidant responses in plants and their influence on phytoremediation process - Mitton, Francesca María (2018)
Phytoremediation is a low cost technology based on the use of plants to remove a wide range of pollutants from the environment, including the insecticide DDT. However, some pollutants are known to enhance generation of reactive oxygen species (ROS), which can generate toxic effects on plants affecting the phytoremediation efficiency. This study aims to analyze the potential use of antioxidant responses as a measure of tolerance to select plants for phytoremediation purposes. Tomato and zucchini plants were grown for 15 days in soils contaminated with DDTs (DDT + DDE + DDD). Protein content, glutathione-S-transferase (GST), glutathione reductase (GR), glutathione peroxidase (GPx) and catalase (CAT) activities were measured in plant tissues. Exposure to DDTs did not affect protein content or CAT activity in any of the species. GST, GR and GPx activity showed different responses in exposed and control tomato plants. After DDTs exposure, tomato showed increased GR and GPX activity in stems and leaves, respectively, and a decrease in the GST activity in roots. As no effects were observed in zucchini, results suggest different susceptibility and/or defense mechanisms involved after pesticide exposure. Finally, both species differed also in terms of DDTs uptake and translocation. The knowledge about antioxidant responses induced by pesticides exposure could be helpful for planning phytoremediation strategies and for the selection of tolerant species according to particular scenarios.